Iconophilia and eschatology - Pereyra, Mario (2016)
Starting from the promulgation of the law of God at Sinai, with the prohibition of do not “making pictures,” this article will review historically the main stages of how the images were acquired greater prominence from the hypermodern times, dominated by the “screens” (TV, GPS, PC, mobile, etc.) and a hipervisual globalized culture, which could be called iconophilia, very close to the iconolatry, which places us at the antipodes of Sinai. From this context, the concept of “image” is analyzed in the book of Revelation and, especially, the interpretation of the theologian Jon Paulien, who interprets the third beast of Rev 13 —which emerges from the earth— as a counterfeit of the Holy Spirit. Traditionally, Adventist theology has identified this beast as the United States. The purpose of this power is to make “great signs, even causing fire to come down from heaven to the earth in full view of the people,” fooling to the “inhabitants of the earth.” We know that this will be possible through Washington’s policy, but is also likely to intervene Hollywood (with its film productions) and Silicon Valley, the center most important in the world of cyber technology and virtual reality; the largest exhibitors the culture of the current image potentially capable of performing these miracles shocking